Analysis of Factors Influencing the Effectiveness of School-Based Management (SBM) - Mohzana Mohzana (International Journal of Educational Narratives, 2025)
Background. The implementation of School-Based Management (SBM) aims to enhance the quality of education by decentralizing decision-making and promoting school autonomy. However, its effectiveness is influenced by various internal and external factors. Purpose. This research examines the key factors affecting the success of SBM in schools. The primary objective is to identify and analyze these factors, which include leadership, teacher involvement, community participation, and resource management. Method. A mixed-methods approach was used, combining qualitative interviews with school principals, teachers, and education officials, and quantitative data gathered through surveys distributed to stakeholders. Results. The findings reveal that strong leadership, effective teacher collaboration, active community engagement, and adequate resources significantly contribute to the effectiveness of SBM. However, challenges such as insufficient training and limited access to resources hinder its full implementation. Conclusion. The study concludes that for SBM to be effective, schools must invest in professional development, enhance communication between stakeholders, and ensure better resource allocation. The research offers recommendations for policy makers and school administrators to improve the SBM framework and achieve more effective educational outcomes.